Day 2 Thu, March 02, 2023 2023
DOI: 10.2523/iptc-22878-ms
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Novel Silane Coated Nanoparticles as an Additive for High-Performance Drilling Fluid Applications

Abstract: Improving water-based drilling fluid properties to mitigate instability issues at elevated temperatures is the need of the hour. In this study, industrially prepared silica nanoparticles (NPs) coated with AEAPTS ([3-(2-Aminoethylamino) propyl] trimethoxy silane) was used as an additive to enhance the rheology and control filtration of the water-based mud. Silica nanoparticles were coated separately in a two-step process, which involved the addition of a hydroxyl group first and then coating with AEAPTS. To che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Filtration occurs, leaving solids on the wellbore wall, forming a mud cake that stabilizes the wellbore and reduces fluid loss. The challenge is to minimize formation damage while achieving a thin, impermeable mud cake, balancing the need for stability and fluid retention in the drilling system …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Filtration occurs, leaving solids on the wellbore wall, forming a mud cake that stabilizes the wellbore and reduces fluid loss. The challenge is to minimize formation damage while achieving a thin, impermeable mud cake, balancing the need for stability and fluid retention in the drilling system …”
Section: Resultsmentioning
confidence: 99%
“…This increased surface area provides sites for potential bonding with functional groups, which can profoundly impact chain entanglement and, consequently, bestow a diverse array of properties upon the matrix. Consequently, the NPs may establish direct or intermediary chemical linkages with the base fluid, thereby enhancing the PV of the WBMs. , It is worth noting, however, that the presence of CuO NPs induces a repulsive force with the water molecules. This phenomenon led to a reduction in the PV as NP concentration escalated primarily due to the intensified repulsive forces. , In addition, Dejtaradon et al and Liu et al supplemented a similar observation of decreasing PV with an explanation of the reduced mechanical friction due to the presence of NPs in the drilling fluid system. , This effect is particularly crucial in the context of drilling fluids, where it plays a vital role in preserving fluid viscosity under conditions of elevated pressure and temperature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drilling fluids are used in oil and gas and geothermal energy drilling operations to perform a variety of tasks, including removing drill cuttings, cooling and lubricating the drill bit, and supplying hydrostatic pressure to ensure borehole stability. The execution of these tasks depends on the lithology being drilled and a number of drilling fluid parameters that need to be optimized to achieve desired performance water base muds (WBM) have had various additives added to them to enhance performance. , These materials, which include natural polymers like xanthan gum, are employed to develop rheological and filtration properties and to reduce wellbore instability issues. The thermal stability of these polymers becomes a noteworthy concern, as well as a technical and economic concern, as the well depth and bottom hole temperatures rise. Furthermore, it has been suggested that dispersing nanoparticles into drilling mud might enhance its performance, particularly in downhole circumstances. Therefore, further technological developments are required to address the high-pressure and high-temperature (HPHT) issues and minimize drilling problems .…”
Section: Introductionmentioning
confidence: 99%